In Memoriam: Cytogeneticist Dr. Sc. Ninel A. Petrova (1940–2024) — life and scientific heritage - Valentina Kuznetsova; Paraskeva Michailova; Andrey Przhiboro; Natalia Khabazova (Comparative Cytogenetics)
The article is dedicated to the memory of Dr. Sc. Ninel A. Petrova, who passed away on 18 April 2024, and to her scientific heritage. Ninel was born on 28 March 1940 in Leningrad, the former Soviet Union. From 1959 to 1964, she studied at the Faculty of Biology and Soil Science of the Leningrad State University. After graduating from the university, Ninel joined the Zoological Institute of the Russian Academy of Sciences, where she worked for almost 60 years, rising from a research assistant to a leading researcher. Her scientific research focused on the structure and evolution of polytene chromosomes of two families of Diptera, black flies (Simuliidae) and non-biting midges (Chironomidae). Ninel has published nearly 200 scientific articles, three monographs and one monograph chapter and has become one of the leading experts in her field. Along with scientific activities, Ninel worked for 25 years as the Scientific Secretary of the Specialized Scientific Council for the Defense of Dissertations at the Zoological Institute.